2020
DOI: 10.1029/2020gl088920
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphy of Ice and Ejecta Deposits at the Lunar Poles

Abstract: Water ice has been delivered to the lunar poles from different sources over billions of years, but this accumulation was punctuated by large impacts that excavated dry regolith from depth and emplaced it in layers over the poles. Here, we model the resulting stratigraphies of ice and ejecta deposits in the lunar polar regions. Large polar craters were age dated, and their ejecta distributions calculated with standard scaling relations. We then created a Monte Carlo model for ice deposition and ejecta emplaceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 84 publications
(140 reference statements)
6
62
0
Order By: Relevance
“…Although aforementioned processes most certainly contribute to observe polar hydrogen abundance in general, as can be clearly seen by the fuzzy region of hydrogen abundance in Figure 8, we suspect that local asteroidal and cometary impacts are most likely the source of delivery to the regions with distinctively larger hydrogen abundance. This finding agrees with modeling results in the study by Cannon et al (2020). Here, we suggest that possible impactors mainly contribute to the immediate vicinity of the impact site for the same reasons as stated above; nearby PSRs would otherwise show enhanced hydrogen signals as well.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although aforementioned processes most certainly contribute to observe polar hydrogen abundance in general, as can be clearly seen by the fuzzy region of hydrogen abundance in Figure 8, we suspect that local asteroidal and cometary impacts are most likely the source of delivery to the regions with distinctively larger hydrogen abundance. This finding agrees with modeling results in the study by Cannon et al (2020). Here, we suggest that possible impactors mainly contribute to the immediate vicinity of the impact site for the same reasons as stated above; nearby PSRs would otherwise show enhanced hydrogen signals as well.…”
Section: Discussionsupporting
confidence: 92%
“…Despite the fact that they are in direct vicinity, Shackleton shows no distinct sign for hydrogen. Modeling results from Cannon et al (2020) show similar results and suggest that the relatively younger age of Shackleton could be the reason for the lack of significant water ice.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Deutsch et al (2020) showed that spectral evidence of surface ice is concentrated within the permanent shadowed regions of craters older than the Copernican era, while Copernican craters are relatively ice-poor. Cannon et al (2020) showed that large ancient impacts may have produced layers of ice and ejecta to fill ancient craters and Needham and Kring (2017) showed how ancient volcanic outgassing may have provided large quantities of water to the lunar poles 3.5 billion years ago. If the majority of lunar ice is ancient (older than 3 Ga), then it will have been depleted by in-situ reworking at least as deeply as 3 m and pulverized in the degradation zone at least as deeply as 10 m over the last 3 Ga (Figure 6).…”
Section: Implications For Polar Icementioning
confidence: 99%
“…Impacts follow a negatively sloped power law; thus, numerical modeling of concurrent larger and smaller-scale processes requires exponentially more simulated impactors as the scale range increases. The simulation by Cannon et al (2020) assumed small-scale gardening like that we model here evenly processes the top meter in their simulations. Similar applications of our analytical gardening model to simplify more computationally expensive numerical modeling may be useful moving forward.…”
Section: Implications For Polar Icementioning
confidence: 99%